Confidence to Return to Play After ACL Reconstruction: An Evaluation of Quadriceps Strength Symmetry and Injury Mechanism in Male Athletes. (September 2022) - Straub, Rachel K.; Della Villa, Francesco; Mandelbaum, Bert; Powers, Christopher M.
Background: After anterior cruciate ligament reconstruction (ACLR), diminished quadriceps strength symmetry and reduced psychological readiness to return to play (RTP) increase the risk for subsequent injury. Although the relationship between quadriceps strength symmetry and psychological readiness to RTP has been reported to be influenced by injury mechanism in female athletes, it is unclear whether such a relationship exists in male athletes. Hypothesis: Quadriceps strength symmetry would be positively associated with greater psychological readiness to RTP after ACLR, regardless of injury mechanism. Study Design: Retrospective cohort. Level of Evidence: Level 3 (cohort study). Methods: Sixty male patients completed strength testing and the Injury-Psychological Readiness to Return to Sport Scale (I-PRRS) at an outpatient clinical facility as part of return to sport testing after ACLR. Linear regression analysis was used to assess the relationship between the I-PRRS and the independent variables of interest (quadriceps strength symmetry and injury mechanism). Results: For all patients combined, no symmetry × mechanism interaction was found ( P = 0.11). A significant positive relationship was found between quadriceps strength symmetry and the I-PRRS score ( P < 0.001, R 2 = 0.31), after adjusting for time post-ACLR and injury mechanism. Conclusion: Greater quadriceps strength symmetry was associated with greater psychological readiness to RTP after ACLR in male athletes. In contrast to what has been reported in female athletes, this relationship was independent of injury mechanism. Clinical Relevance: Given the potential negative consequences of quadriceps strength deficits on one's confidence to RTP, the need to restore quadriceps symmetry during the postoperative period is readily apparent. Low confidence or low psychological readiness to RTP may be indicative of quadriceps strength asymmetry or poor physical function in general.